DYNAMICS AND FORMING OF CONTINENTAL CRUST AT PRECEMBRIAN - PERCHUK, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
A new model оf gravitational redistribution of rocks within the Precambrian crust, which might have been triggered by a mantlederived plume has been developed. The model was multidisciplinary tested for granulite complexes (HGT) located within cratons (GSB). The HGT are always younger than the adjacent GSB and their lithologies are chemically identical to those from the GSB. Both the IC and the DC paths can be identified in the same HGT. The IC path characterizes the contact of the HGT with the GSB, while DC paths are common P-T paths for the rocks located far from this contact. Mineral equilibria from the juxtaposed GSB in the footwall sections of the bounding shear zones record P-T loops: peak P-T conditions were reached at the lowest P-T conditions recorded by the adjacent granulites. This model suggests synchronous movement of GSB during exhumation of the adjacent HGT and their identical isotopic ages. While granulites move up to the surface, cool metabasalts and metakomatiites move down, cooling the granulites along the contact zone. The existence of both DC and IC paths in the same granulite complex can thus be explained by differences in the movement of different granulite "blocks" during exhumation. In many HGT the Archaean granulites were not exhumed to the surface until hundreds of millions years later. The gravitational redistribution model has been tested by 2D numerical simulation showing that the granulite facies terrains may have develop as crustal scale intrusive-shaped bodies during 10 My. Tectonospheric by seismic tomography, supports the model.